Composition and distribution characteristics of invasive alien species in Tieu Can district, Tra Vinh province - Trung, Hoàng Đình (Hue University Journal of Science: Natural Science, 2021)
This research was carried out from December 2019 to May 2020 in 11 major sites in Tieu Can district. Sixteen alien species belonging to 15 genera, 13 families, 11 orders of the 5 phyla: Magnoliophyta, Oomycota, Mollusca, Arthropoda, and Chordata were identified. Eleven are invasive alien species (68.75%), and the rest is potential invasive alien species (31.25%). We focus on five common species that substantially affect agriculture, forestry, and aquaculture.